The Currency of Ruy Mauro Marini’s Thinking and Dependency Theory / La Vigencia del Pensamiento de Ruy Mauro Marini y la Teoría de la Dependencia - Valencia, Adrián Sotelo (Textos & Contextos (Porto Alegre), 2017)
Ruy Mauro Marini’s thinking, within the framework of Marxism, continues to apply in the 21st century because the conditions he discovered around the dialectics of dependency (super-exploitation of labor, unequal exchange, sub-imperialism, and the Fourth Power) remain in the contours of the world capitalist economy.